Minimal residual disease detection by next-generation sequencing of different immunoglobulin gene rearrangements in pediatric B-ALL - Haipin Chen; Miner Gu; Juan Liang; Hua Song; Jingying Zhang; Weiqun Xu; Fenying Zhao; Diying Shen; Heping Shen; Chan Liao; Yongmin Tang; Xiaojun Xu (Nature Communications, 2023)
Abstract While the prognostic role of immunoglobulin heavy chain locus (IGH) rearrangement in minimal residual disease (MRD) in pediatric B-acute lymphoblastic leukemia (B-ALL) has been reported, the contribution of light chain loci (IGK/IGL) remains elusive. This study is to evaluate the prognosis of IGH and IGK/IGL rearrangement-based MRD detected by next-generation sequencing in B-ALL at the end of induction (EOI) and end of consolidation (EOC). IGK/IGL rearrangements identify 5.5% of patients without trackable IGH clones. Concordance rates for IGH and IGK/IGL are 79.9% (cutoff 0.01%) at EOI and 81.0% (cutoff 0.0001%) at EOC, respectively. Patients with NGS-MRD < 0.01% at EOI or <0.0001% at EOC present excellent outcome, with 3-year event-free survival rates higher than 95%. IGH-MRD is prognostic at EOI/EOC, while IGK-MRD at EOI/EOC and IGL-MRD at EOI are not. At EOI, NGS identifies 26.2% of higher risk patients whose MRD < 0.01% by flow cytometry. However, analyzing IGK/IGL along with IGH fails to identify additional higher risk patients both at EOI and at EOC. In conclusion, IGH is crucial for MRD monitoring while IGK and IGL have relatively limited value.